Determinants of foreign direct investment across provinces in China. - Ho, Liang Jiat. (2008)
The study seeks to identify the risks banks faced with the adoption of Internet banking and whether it has any impact on existing banking risks. Current publications focussed mainly on security issues of Internet banking. However, this research intends to determine the other important risks that banks need to investigate prior to the implementation of this new technology. Interviews were conducted to solicit opinions from the banking lecturers in NTU and professionals in the industry.